Effects of Land Use Change Related to Small-Scale Irrigation Schemes in Kilombero Wetland, Tanzania - Alavaisha, Edmond; Mbande, Victor; Börjeson, Lowe; Lindborg, Regina (Frontiers in Environmental Science, 2021)
Increasing agricultural land use intensity is one of the major land use/land cover (LULC) changes in wetland ecosystems. LULC changes have major impacts on the environment, livelihoods and nature conservation. In this study, we evaluate the impacts of investments in small-scale irrigation schemes on LULC in relation to regional development in Kilombero Valley, Tanzania. We used Remote Sensing (RS) and Geographical Information System (GIS) techniques together with interviews with Key Informants (KI) and Focus Group Discussion (FGD) with different stakeholders to assess the historical development of irrigation schemes and LULC change at local and regional scales over three decades. Overall, LULC differed over time and with spatial scale. The main transformation along irrigation schemes was from grassland and bushland into cultivated land. A similar pattern was also found at the regional valley scale, but here transformations from forest were more common. The rate of expansion of cultivated land was also higher where investments in irrigation infrastructure were made than in the wider valley landscape. While discussing the effects of irrigation and intensification on LULC in the valley, the KI and FGD participants expressed that local investments in intensification and smallholder irrigation may reduce pressure on natural land cover such as forest being transformed into cultivation. Such a pattern of spatially concentrated intensification of land use may provide an opportunity for nature conservation in the valley and likewise contribute positively to increased production and improve livelihoods of smallholder farmers.